Mergulho recreativo na região metropolitana de Fortaleza (NE, Brasil): subsídios para o desenvolvimento sustentável - Pantalena, Ana Flávia (2017)
Recreational diving is one of the multiple activities in coastal zones. In the last 10 years, this activity has seen increased contribution to the economies of various seaside cities. The objective of this study was to characterize and diagnose the recreational diving activities in the metropolitan region of Fortaleza (MRF). The methodology consisted of an analysis of the environmental awareness of recreational divers in regards to the diving spots (e.g. marine biodiversity, environmental impacts, diving areas), as well as the services and infrastructure offered. Bibliographic research was performed along with interviews and questionnaires (n=140) to analyze the history of diving in recent decades. The results suggest that although there are 32 diving spots near the coast, only the Marine Protected Area (Pedra da Risca do Meio Marine State Park) with its tropical reefs (assessed as “Good/Very Good” regarding marine biodiversity) is visited regularly. The negative aspects were travel time to the diving spots, trash, and abandoned fishing nets and lines. The boat and embarkation/disembarkation sites were classified as “Bad/Poor.” The respondents believe improving services (21.1%), establishing new diving spots (20.7%), better prices (17%) and more propaganda (16%) would be incentives to dive more regularly in the metropolitan region of Fortaleza. Among the actions proposed are new diving spots, creation of marine diving trails near the coast, environmental education classes "pre-dive", improvement of the infrastructure of the services offered and development of partnerships between the various sectors involved aiming greater disclosure and encouragement for the activity. Given the lack of information on this topic in the state and in developing countries, the results of this study offer new, previously unpublished information. In addition, it can be used in the preparation of public policies on environmental education and the sustainable management of marine environments. These policies should benefit not only the marine ecosystem but also all users involved directly or indirectly in the production chain and in the sustainable use of the coastal zone.